Impact of Organizational Brand-Building Strategies on Organizational Brand Equity: A Moderating Role of Brand-Oriented Leadership - Wei, Zhang (Frontiers in Psychology, 2022)
In this era of competition, branding is an essential marketing tool for organizations to compete in today’s dynamic markets. Organizations must realize the importance of employee-based brand equity from the perspectives of customer branding and financial performance. Employee-based brand equity plays a crucial role in building organizational brand equity. This study conceptualized a model that helps the practitioners to build employee-based brand equity and organizational brand equity. This study examines the role of organizational brand-building strategies and brand-oriented leadership to promote employee-based brand equity and organizational brand equity. This study collected data from the employees of various beverage companies in China. This study analyzed data through partial least square structural equation modeling using SmartPLS 3. This study found a positive direct association between organizational brand building strategies and employee-based brand equity, but no direct association was found between organizational brand building strategies and organizational brand equity. This study also confirms that organizational brand-building strategies indirectly promote organizational brand equity through employee-based brand equity. Moreover, this study demonstrates that brand-oriented leadership directly influences employee-based brand equity and organizational brand equity but negatively moderates the relationship between organizational brand-building strategies and employee-based brand equity. No moderation was found in the relationship between organizational brand-building strategies and organizational brand equity. Finally, the practical and theoretical implications of this study are discussed.